Предмет: Математика,
автор: kukuska099111
(11a+3b)(11a-3b)-(11a-3b)(3b-11a)
упростите выражения
пожалуйста с обьяснением
Ответы
Автор ответа:
2
Ответ:
Пошаговое объяснение:
^2 во второй степени
(11a+3b)(11a-3b) - (11a-3b)(3b-11a) =
общий множитель
[ (11a+3b) - (3b-11a) ] (11a-3b) =
[ 11a+3b - 3b +11a ] (11a-3b) =
22a (11a-3b) =
242a^2 -66ab)
Похожие вопросы
Предмет: ОБЖ,
автор: jdhdychhdhrjirjfjjfj
Предмет: Українська мова,
автор: Irina890000
Предмет: Музыка,
автор: yuraruzak473
Предмет: Алгебра,
автор: viktretiack201
Предмет: Биология,
автор: Vikane27